Association between triglyceride-glucose index and Helicobacter pylori infection: a cross-sectional study - Long, Dan; Mao, Chenhan; Xu, Yin; Zhu, Ying (Frontiers in Endocrinology, 2025)
BackgroundMounting research suggests that insulin resistance (IR) is associated with Helicobacter pylori (H. pylori) infection. The triglyceride-glucose (TyG) index has received widespread attention due to its high sensitivity in assessing IR. This study examined the association between H. pylori infection and TyG index.MethodsThis cross-sectional study used data from the National Health and Nutrition Examination Survey (NHANES) 1999 - 2000. Participants were categorized into quartile groups (Q1–Q4) based on their TyG index. Weighted multivariable-adjusted logistic regression and subgroup analysis were used to explore the correlation between TyG index and H. pylori infection. Furthermore, sensitivity analysis was conducted to assess the robustness of our findings.ResultsThis study included 2,918 participants, 1,101 of whom were infected with H. pylori. The mean TyG index for all participants was 8.56 ± 0.67. Patients who were H. pylori positive had higher levels of TyG index compared with H. pylori seronegative participants (8.74 ± 0.03 vs. 8.57 ± 0.03, P < 0.05). The fourth quartile of the TyG index showed the highest odds of H. pylori infection compared to Q1 (OR = 2.37, 95%CI: 1.52 to 3.71, P  <  0.001). Sensitivity analysis indicated that the association between TyG index and H. pylori infection remained strong even after excluding participants with cardiovascular diseases or taking lipid-lowering medications, as well as patients with diabetes or taking glucose-lowering medications.ConclusionsIn this study, a stable and strong positive association was found between TyG index and H. pylori infection. IR may be significantly associated with H. pylori infection. Further studies are necessary to elucidate the underlying mechanisms and potential clinical implications of these findings.